Analisis Pendapatan Usahatani Biofarmaka dan Kontribusinya Terhadap Total Pendapatan Petani di Kabupaten Simalungun, Provinsi Sumatera Utara - Hotden Leonardo Nainggolan; Maria Rumondang Sihotang; Albina Ginting (AGRIMOR, 2022)
Apart from being an ingredient for medicinal plants, biopharmaceuticals also act as a source of community income. The purpose this study was to analyze the farm income of biopharmaceutical crops and their contribution to income of farmers. Area of study was conducted in Sub-district of Dolok Masagal, from February-May 2021. The population of this study were farmers who managed biopharmaceutical farming with 436 families. The research sample was determined intentionally with 30 respondents, and distributed proportionally to 3 out of 10 villages, namely; Dolok Huluan Village 16 respondents, Bangun Pane 12 respondents and Bintang Mariah 2 respondents. This study uses primary data and secondary data, and analyzed by descriptive method. Based on the results of the study concluded; 1) the average income from biopharmaceutical farming is IDR74,504,744/year, the average income from non-biopharmaceutical farming is IDR5,137,692/year and the average income outside of farming is IDR7,496,667/year; 2) farm income of biopharmaceuticals contributed 84.1% to the total income of family farmers, non-biopharmaceutical farm income contributed 5.9%, non-farm income contributed 10% to the total income of farming families. In increasing the income of biopharmaceutical crop farming, it is recommended; 1) so that farmers join farmer groups so that they can easily access seeds, fertilizers, and pesticides/drugs; 2) so that the Agricultural Extension Center of Subdistrict of Dolok Masagal actively provides counseling to farmers for the development of better biopharmaceutical farming; 3) that local governments partner with medicinal plant processing companies to ensure price stability during the harvest season.